ECOLOGIZATION OF RAILWAY TRANSPORT:NEEDS AND DIRECTIONS OF IMPLEMENTATION - KUPALOVA, HALINA; GONCHARENKO, NATALIIA; KORENEVA, NATALIIA; MALINOVSKA, DARIA; VERKHOHLIADOV, SEMEN (Herald of Khmelnytskyi National University. Economic sciences, 2022)
By supporting the European Green Course, Ukraine has committed itself to achieving carbon neutrality by 2060. According to the Strategy of State Environmental Policy of Ukraine for the period up to 2030, the most problematic economic activities in terms of negative environmental impact that need to be reformed and modernized are transport, energy, coal, water and forestry. Railway transport is crucial in the functioning of production and social infrastructure of the regions, economic development, strengthening Ukraine's position in the international economic and trade environment. The development of such industries as agriculture, metallurgical production, coal industry, mining and metallurgical complex, chemical industry, construction, defense depends on railway transport, as stated in the National Transport Strategy of Ukraine for the period up to 2030. Therefore, the greening of rail transport is a priority in the formation of a carbon-neutral transport system of the country, achieving strategic environmental goals and objectives.The article is devoted to the topical problem of greening of railway transport in Ukraine. It is established that it is important in ensuring efficient freight turnover, development and integration of transport infrastructure into the international network, the transition to a carbon-neutral economy in general. The railway is one of the most environmentally friendly modes of transport, but needs further environmental modernization. The main directions of introduction of ecologically friendly technologies which will allow to reduce anthropogenic impact on the environment are formulated. They should cover the use of alternative fuels and energy sources in economic processes, reducing noise load, the introduction of piggyback transportation. Management measures include improving environmental management: development of environmental strategy of JSC "Ukrzaliznytsia", justification of clear environmental goals, improving staff knowledge in the field of environmental protection and implementation of environmental management system. It is substantiated that JSC "Ukrzaliznytsia" will be able to achieve carbon neutrality by 2050.
Keywords: transport; railways; greening; carbon neutrality; anthropogenic impact